Optimisation of therapeutic strategies for ST-segment elevation acute myocardial infarction: the impact of a territorial network on reperfusion therapy and mortality. Issue 5 (24th July 2008) - Saia, F; Marrozzini, C; Ortolani, P; Palmerini, T; Guastaroba, P; Cortesi, P; Pavesi, P C; Gordini, G; Pancaldi, L G; Taglieri, N; di Pasquale, G; Branzi, A; et al.
Abstract : Objective: To assess the clinical impact of a regional network for the treatment of ST-segment elevation myocardial infarction (STEMI). Methods: All patients with STEMI (n = 1823) admitted to any of the hospitals of an area with one million inhabitants during the year 2002 (n = 858)—that is, before the network was implemented, and in 2004 (n = 965), the year of full implementation of the network, were enrolled in this study. The primary evaluation was in-hospital mortality. Secondary outcomes included the incidence of major adverse cardiac and cerebrovascular events (MACCE), defined as death, myocardial infarction, stroke and coronary revascularisation procedures over 1-year follow-up. Results: Between 2002 and 2004, there was a major change in reperfusion strategy: primary angioplasty increased from 20.2% to 65.6% (p<0.001), fibrinolytic therapy decreased from 38.2% to 10.7% (p<0.001) and the rate of patients not undergoing reperfusion was reduced from 41.6% to 23.7% (p<0.001). In-hospital mortality decreased from 17.0% to 12.3% (p = 0.005), and this reduction was sustained at 1-year follow-up (23.9% in 2002 and 18.8% in 2004, p = 0.009). Similarly, the 1-year incidence of all MACCE was reduced from 39.5% in 2002 to 34.3% in 2004 (p = 0.01). Conclusions: Organisation of a territorial network for STEMI is associated with increased rates of reperfusion therapy and reduction of in-hospital and 1-year mortality.